A brief Review of Reverse Shoulder Prosthesis: Arthroplasty, Complications, Revisions, and Development - Ozada, Neriman; Yazdi, Sina Ghafoorpoor; Khandan, Amirsalar; Karimzadeh, Mohammad (Natl Center Trauma Research, 2018)
The shoulder is considered to be an important flexible and movable part in the human body. However, it is a wobble joint as its range of motion (ROM) is high. This unstable status increases the rate of joint injury. The processes leading to shoulder joint dysfunction are arthritis, hemiarthroplasty failure, and pseudoparalysis; in turn, one of the main factors contributing to these problems is rotator cuff tear (RCT). Reverse shoulder arthroplasty (RSA) maybe a proper treatment for shoulder dysfunction and pain. This treatment elevates shoulder movement and has been augmented by recent advances in the development of the reverse shoulder prosthesis (RSP) design. This current review highlights the recent developments, revisions, and complications. A review of the published literature has been done to determine the overall rates of problems, complications, reoperations, and revisions after RSA. Furthermore, this review discusses the problems concerning RSP, shoulder joint replacement, and improvement in shoulder joint movement after arthroplasty.
Keywords: Reverse Shoulder Arthroplasty; Postoperative; Dysfunction; Complications; Development